Webbing the Common Good: Virtual Environment, Incarnated Community, and Education for the Reign of God - Blier, Helen M. (Teaching theology and religion, 2008)
Online technologies, recently embraced by seminaries to respond to changing student needs and demographics, compel practitioners to ask questions about the content, methods, and desired outcomes of teaching/learning experiences. Indeed, as Delamarter and Brunner have pointed out in this journal (2005), many seminaries have turned to these strategies only to find that the issues are not technological; rather, they are pedagogical. This article discusses the insights generated by one such teaching experiment, a hybrid course on religious education for social justice. Through this educational experiment, the professor and students discovered that the format of the hybrid course proved to be an effective means by which to promote the praxis of social justice as well as develop some of the skills essential for effective ministry and education. The article begins with the rationale of the course design and content and continues with the perspectives of the students and instructor in reflection on the experiment. It concludes with some preliminary insights into the potential usefulness of hybrid learning for both peace and justice education as well as its value in the overall formation of educators and ministers.